The Relationship Between Knowledge And Anthropometric Measurement Skills In Cadres In The Meureubo Health Center Working Area, West Aceh Regency, Meulaboh 2023 - Laila Apriani Hasanah Harahap; Itza Mulyani; Adico Notarza Aulia; Enda Silvia Putri; Cukri Rahma; Eva Flourentina Kusuma Wardani; Renita Fransisca Siahaan (The International Science of Health Journal, 2024)
Nutritional problems in Aceh, especially West Aceh, include stunting, wasting, underwight and overwight which until now nutritional status. There is a relationship between knowledge and anthropometric measurement skills in cadres with p value 0,000 where good knowledge will create awareness someone and finally trigger someone with the appropriate skills with knowledge. Respondents who have good knowledge and finally trigger someone with the appropriate skills with knowledge. Respondents who have good knowledge towards anthropomeric measurements, namely 28 respondents (44.4 %). It is suggested that posyandu cadres make posters contains appropriate measurements and weighing standards, in order to serve as a reference for making measurements